# Solve for p 6p-8-4p+7-3=-4p+5

6p-8-4p+7-3=-4p+5
Simplify 6p-8-4p+7-3.
Subtract 4p from 6p.
2p-8+7-3=-4p+5
2p-1-3=-4p+5
Subtract 3 from -1.
2p-4=-4p+5
2p-4=-4p+5
2p-4=-4p+5
Move all terms containing p to the left side of the equation.
Add 4p to both sides of the equation.
2p-4+4p=5
6p-4=5
6p-4=5
Move all terms not containing p to the right side of the equation.
Add 4 to both sides of the equation.
6p=5+4
6p=9
6p=9
Divide each term by 6 and simplify.
Divide each term in 6p=9 by 6.
6p6=96
Cancel the common factor of 6.
Cancel the common factor.
6p6=96
Divide p by 1.
p=96
p=96
Cancel the common factor of 9 and 6.
Factor 3 out of 9.
p=3(3)6
Cancel the common factors.
Factor 3 out of 6.
p=3⋅33⋅2
Cancel the common factor.
p=3⋅33⋅2
Rewrite the expression.
p=32
p=32
p=32
p=32
The result can be shown in multiple forms.
Exact Form:
p=32
Decimal Form:
p=1.5
Mixed Number Form:
p=112
Solve for p 6p-8-4p+7-3=-4p+5

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top